Blurring Boundaries: Socio-Spatial Consequences of Working at Home - (:unkn) unknown (My University, 1987)
This report looks at a cross-section of professional home workers in various occupations, both self-employed and corporate-employed. It identifies patterns of divergent activities within the home and assesses their success or hindrance in accommodating multiple roles in the same place. Funded by a grant from the National Endowment for the Arts.